O Pacto Nacional pela Alfabetização na Idade Certa - PNAIC e a formação de professores alfabetizadores - Scolaro, Julian Monike Nazario (2020)
This work aims to analyze, within the scope of educational policies, the National Literacy Pact at the Right Age - PNAIC, which had its genesis with Decree No. 6.094 of April 24, 2007, which regulates the implementation of the Commitment Goals Plan “Todos pela Educação” (All for Education) with a view to social mobilization for the improvement of Basic Education and instituted through Ordinance No. 867 of July 4, 2012, which aimed to outline guidelines for the training of literacy teachers. It was investigated, in this way, that the Brazilian educational policy went through international influences, which culminated in the Basic Education Reform process since 1990, which reconfigured the Brazilian educational scenario, based on the ideological political discourse of the bourgeoisie, moment, embraces the new form of capital, the Neoliberal. The present research identified the relationships that permeated the construction of the PNAIC, as well as this Pact was configured in the year 2012 to 2019. In this direction, the investigation process was based methodologically on primary and secondary sources. The central official documents analyzed were the National Pact for Literacy at the Right Age - PNAIC Manual 2012, the Guidance Documents from 2014 to 2017, which organized the implementation and development of the program in the education networks, and the documents from the Ministry of Education , ordinances and resolutions. We also used a theoretical framework produced by researchers in the field and who helped us in the process of reflection and systematization of this and work. It was possible to verify that the PNAIC throughout its seven years of execution, this program has changed several times with regard to the guidelines for the training of literacy teachers and, at first, the program reached a considerable number of teachers, but over the years, teachers' adherence to the program gradually declined, given the change in the criteria for participation established by the Ministry of Education.